Peran Bahan Ajar Digital Sejarah Perkebunan Karet Berbasis Experiential Learning Dalam Meningkatkan Sikap Kewirausahaan Peserta Didik SMK Negeri 5 Bandar Lampung - Monalisa Monalisa; Muhammad Akhyar; Musa Pelu (Universitas Sebelas Maret, 2022)
The economy of Indonesian society and the unemployment rate of school leavers increased and with the coronavirus outbreak that required many workers to be laid off. This problem became the center of attention in the era of the covid-19 outbreak. This research is shown to obtain an overview of the entrepreneurial attitude of learners in implementing digital historical learning-based learning materials. The method used in this study is a qualitative method. The type of data used is primary data through interviews to teachers and questionnaire scales to learners to find out entrepreneurial attitudes. As well as literature studies relevant to the research title for literature review. The results of the study are digital teaching materials about the history of rubber plantations based on experiential learning is very good applied to learners in providing entrepreneurial discussion and observation experience for the nation's economic problems into indonesia's golden generation.